Farmers’ Suicides an Impediment to Social Development in India: A Study of Karnataka State - Gyanappa. Huddar, Purnanand Nagappa. Sangalad, Malakajappa (Recent Research in Science and Technology, 2010)
Mahatma Gandhi said that â€˜India lives in villagesâ€™. It is true that majority of our people live in the villages engaged mainly in agriculture and allied activities as the main source of their income. As a key to Indian economy agriculture plays a significant role in the socio-economic development of the country and socio - cultural life of our people. The rainfall in India is unpredictable. Failure of monsoon results in the failure of crops, as a result the farming community fails to pay back the debt they have taken from different financial institutions and private money lenders. They are over burdened with principal amount and interest. This brings misery, helplessness and frustration among farmers, specially small scale and marginal scale farmers. As a result some farmers may take an extreme step of ending their life. The phenomenon of suicide among farmers in India was noticed from 1997 and onwards from Telangana region in Andhra Pradesh, where pesticides used by farmers failed to control the pests due to adulteration which resulted in the loss of crops. This loss of crops drove the farmers to suicide.Â The union and the stateÂ governments have taken various confidence building measures likeÂ waiving of the loan of small and marginal farmers, extension of subsidy on fertilizers, providing agricultural loan at 3 per cent interest through cooperative institutions, Apart from the above, measures should be taken for the effective implementation of crop insurance scheme, health insurance schemes, educating the farmers about crop growing patterns and other measures may develop confidence in the farmers and they may not take extreme step of ending the life.